Utilization of probiotics modulating the gut-brain axis in bipolar disorder and ADHD: a case report - Parikh, Parinda; Singh, Shaurya Kumar; Suthar, Himani J.; Oza, Mina; Mineo, Amanda (International Journal Of Community Medicine And Public Health, 2025)
Bipolar disorder (BD) and attention-deficit/hyperactivity disorder (ADHD) frequently co-occur, complicating treatment due to overlapping symptoms and limited efficacy of conventional pharmacotherapy. Emerging evidence indicates gut dysbiosis in neuropsychiatric pathophysiology via the gut-brain axis, suggesting probiotics as a potential adjunctive intervention. However, their utility in comorbid BD-ADHD remains unexplored. A 15-year-old male with comorbid BD and ADHD exhibited persistent manic symptoms (YMRS:42/60) and hyperactivity despite treatment with aripiprazole and lamotrigine. While manic symptoms improved post-treatment (YMRS:9/60), ADHD-related impulsivity and behavioral dysregulation remained, as shown by the Vanderbilt ADHD scales. Adjunctive probiotics were initiated due to familial preference against stimulant medication. Over 18 months, clinical improvement in both ADHD-related symptoms and residual behavioral dysregulation, as evidenced by follow-up scale scores. This case highlights probiotics as a potential adjunctive therapy for comorbid BD-ADHD, potentially modulating the gut-brain axis pathways to address residual symptoms unresponsive to conventional pharmacotherapy. Further controlled trials are needed to validate microbiota-targeted interventions in complex neuropsychiatric comorbidities.